2013
DOI: 10.1016/j.heares.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Coding of vocalizations by single neurons in ventrolateral prefrontal cortex

Abstract: Neuronal activity in single prefrontal neurons has been correlated with behavioral responses, rules, task variables and stimulus features. In the non-human primate, neurons recorded in ventrolateral prefrontal cortex (VLPFC) have been found to respond to species-specific vocalizations. Previous studies have found multisensory neurons which respond to simultaneously presented faces and vocalizations in this region. Behavioral data suggests that face and vocal information are inextricably linked in animals and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…An additional 8 units exhibited a significant change in neural activity for both vocal-signal and vocal-motor portions of the behavior. Given that previous studies of rhesus monkeys (Gifford et al 2005;Plakke et al 2013a;Romanski et al 2005) and squirrel monkeys (Newman and Lindsley 1976) have all reported neurons responsive to vocalizations in the same areas of frontal cortex, the relatively weak sensory responses to vocal-signal stimuli across marmoset frontal cortex were somewhat surprising. Despite the weak responses to vocalization stimuli, we performed further analyses in parallel with vocal-motor responses to test whether effects at a population level might reveal key differences in neuronal patterns suggestive of why sensory responses were limited during this natural behavior.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…An additional 8 units exhibited a significant change in neural activity for both vocal-signal and vocal-motor portions of the behavior. Given that previous studies of rhesus monkeys (Gifford et al 2005;Plakke et al 2013a;Romanski et al 2005) and squirrel monkeys (Newman and Lindsley 1976) have all reported neurons responsive to vocalizations in the same areas of frontal cortex, the relatively weak sensory responses to vocal-signal stimuli across marmoset frontal cortex were somewhat surprising. Despite the weak responses to vocalization stimuli, we performed further analyses in parallel with vocal-motor responses to test whether effects at a population level might reveal key differences in neuronal patterns suggestive of why sensory responses were limited during this natural behavior.…”
Section: Resultsmentioning
confidence: 95%
“…One neocortical region that has undergone considerable change over primate evolution is frontal cortex (Semendeferi et al 2001), a substrate known to be involved in many complex aspects of human cognition and communication (Fuster 2008;Gabrieli et al 1998;Miller and Wallis 2012). Although aspects of communication signal processing in frontal cortex appear shared across humans and other NHPs (Averbeck and Romanski 2006;Cohen et al 2007;Gifford et al 2005;Plakke et al 2013a; Romanski and Averbeck 2009;Romanski et al 2005), the role of this neocortical substrate in NHP vocal production is more controversial. Much of the data on frontal cortex function during NHP vocal communication comes from studies of restrained animals (Averbeck and Romanski 2006;Cohen et al 2007;Gifford et al 2005;Romanski et al 2005).…”
mentioning
confidence: 99%
“…AL is part of the ventral auditory pathway; a pathway that is thought to mediate non-spatial sound perception (i.e., “what is the sound?”) (Bizley and Cohen, 2013; Plakke et al, 2013b; Rauschecker and Tian, 2000; Rauschecker and Scott, 2009; Romanski, 2004; Romanski and Averbeck, 2009). Consequently, neurons in different regions of this pathway have been tested for their sensitivity to vocalizations (Averbeck and Romanski, 2004, 2006; Cohen et al, 2007; Gaucher et al, 2013; Gifford et al, 2005; Kikuchi et al, 2010; Kusmierek and Rauschecker, 2009; Kusmierek et al, 2012; Perrodin et al, 2011; Petkov et al, 2008; Plakke et al, 2013b; Poremba et al, 2013; Romanski and Goldman-Rakic, 2002; Russ et al, 2008b; Tian et al, 2001). In particular, AL neurons respond robustly to specific vocalizations and, relative to other control stimuli, respond preferentially to vocalizations, (Kusmierek et al, 2012; Rauschecker and Tian, 2000; Russ et al, 2008b; Tian et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Other areas show a greater degree of stimulus selectivity, such as neurons in the anterior portions of the temporal lobe, which are highly selective for individual vocalizations, and the voice of specific vocalizers. Finally, activity in the ventrolateral prefrontal cortex (vlPFC) seems to represent a processing stage beyond that of sensory processing since vlPFC activity reflects non-spatial auditory attention, auditory working memory, sound meaning, and multimodal sensory integration (Cohen et al, 2009; Gifford III et al, 2005; Lee et al, 2009a; Ng et al, 2013; Plakke et al, 2013a; Plakke et al, 2012; Plakke et al, 2013b; Poremba et al, 2004; Romanski et al, 2005; Romanski and Goldman-Rakic, 2002; Russ et al, 2008a; Russ et al, 2008b). …”
Section: Representation Of Auditory Objectsmentioning
confidence: 99%